Orthotylus sicilianus n. sp. (Heteroptera: Miridae). - Wagner, Eduard (Beiträge zur Entomologie = Contributions to Entomology, 1954)
Nomenklatorische Handlungensicilianus Wagner, 1954 (Orthotylus), spec. n.